2002
DOI: 10.1055/s-0037-1613195
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Thrombin Generation in Plasma by Fibrin Formation (Antithrombin I)

Abstract: SummaryThe adsorption of thrombin to fibrin during clotting defines “Antithrombin I” activity. We confirmed that thrombin generation in afibrinogenemic or in Reptilase defibrinated normal plasma was higher than in normal plasma. Repletion of these fibrinogen-deficient plasmas with fibrinogen 1 (‘γA/’γA), whose fibrin has two “low affinity” non-substrate thrombin binding sites, resulted in moderately reduced thrombin generation by 29-37%. Repletion with fibrinogen 2 (‘γ´/’γA), which in addition to low affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 18 publications
5
82
2
Order By: Relevance
“…61 Experiments in which thrombin generation was measured in afibrinogenemia plasma and fibrinogen-depleted plasma supplemented with ␥A/␥A fibrinogen or ␥A/␥Ј fibrinogen showed that ␥A/␥Ј fibrinogen had a more profound effect in down-regulating thrombin generation than ␥A/␥A fibrinogen. 62 Future studies should reveal whether and how a 2-fold reduction of the ␥Ј/␥ ratio would influence fibrin formation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…61 Experiments in which thrombin generation was measured in afibrinogenemia plasma and fibrinogen-depleted plasma supplemented with ␥A/␥A fibrinogen or ␥A/␥Ј fibrinogen showed that ␥A/␥Ј fibrinogen had a more profound effect in down-regulating thrombin generation than ␥A/␥A fibrinogen. 62 Future studies should reveal whether and how a 2-fold reduction of the ␥Ј/␥ ratio would influence fibrin formation and degradation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Residues A414 to L427 of the ␥Ј chain have been reported to play a central role in thrombin binding because of the overall negative charge, and sulfation of residues Y418 and Y422 further enhances binding by increasing the net charge. 12,20,22,23 Sabo et al reported that Y422-D425 forms a ␤-turn that is involved in exosite II binding, whereas further interactions occur between Y418 and Y422. 24 Crystal structure data of the complex between thrombin and a ␥Ј V408-L427 peptide indicated that ␥Ј Y418 interacts with residues R126, K235, and K236 on thrombin and that ␥Ј Y422 binds to thrombin residue K240.…”
Section: Thrombin Bindingmentioning
confidence: 99%
“…Reconstitution of fibrinogen into fibrinogen-deficient plasma reduced thrombin generation as measured using a thrombin chromogenic substrate, and ␥A/␥Ј fibrinogen showed more inhibition than ␥A/␥A fibrinogen. 23 Another study using a ␥Ј P410-L427 synthetic peptide found no effects on cleavage of a chromogenic substrate by thrombin, but a reduction in FVIII activation, suggesting selective inhibition of the intrinsic pathway. 31 These data suggest that the ␥Ј chain may act as an inhibitor of the plasma consolidation (intrinsic) pathway for thrombin generation in the solution phase.…”
Section: Thrombin Bindingmentioning
confidence: 99%
“…In some patients increase of prothrombin activation fragments or thrombin-antithrombin complexes has been observed, which may reflect an enhanced thrombin generation [Dupuy et al, 2001;Korte and Feldges, 1994]. Interestingly, an anti-thrombin role has also been attributed to fibrinogen, since in its absence the clearance of thrombin is impaired [de Bosch et al, 2002]. Furthermore, and more importantly, fibrin acts as antithrombin I by both sequestering and downregulating thrombin activity [Mosesson, 2003].…”
Section: Clinical Featuresmentioning
confidence: 99%